10 Sex differences in circumferential and longitudinal strain revealed by strain-encoded cardiac magnetic resonance in healthy volunteers at 1.5T. (26th April 2015) - Clerfond, G; Mangion, K; Carrick, D; Rauhalammi, SM; Corcoran, D; Barrientos, P Hall; McComb, C; McClure, J; Radjenovic, A; Berry, C
Abstract : Background: Displacement encoding with stimulated echoes (DENSE) encodes myocardial tissue displacement into the phase of the MRI image, thus allowing direct quantification of myocardial displacement at multiple cardiac phases. Strain-encoded CMR with DENSE has high spatial (3.2 × 3.2 × 8 mm) and temporal resolution (32.5 ms phase). We aimed to measure myocardial strain values with DENSE in healthy adults across a broad age range at 1.5 Tesla. Methods: Healthy volunteers with no prior medical history (including cardiovascular health problems or medication) were enrolled and underwent CMR at 1.5T (Magnetom Avanto, Siemens Healthcare, Erlangen, Germany). Mid-left ventricular short axis and horizontal long axis DENSE sequences were obtained, and analysed using CIM_DENSE2D software (University of Auckland, New Zealand and Siemens Healthcare). Segmental and global myocardial circumferential and longitudinal strain were obtained. Results: LV dimensions and circumferential strain were available for 75 volunteers (mean age 44.12 ± 17.7 years old, 48% male) (Table 1 ). Longitudinal strain was acquired in a subset of participants (n = 20). Mean global circumferential (Ecc) and longitudinal (Ell) strain were greater in women than in men. These differences were mainly related to strain values in the inferior, infero-lateral and antero-lateral LV segments for the circumferential strain and the apico-lateral segment for the longitudinal strain where LV displacement is greatest. Conclusion: Strain-encoded CMR with DENSE has revealed sex differences in myocardial contractility in healthy adults. Funding: Medical Research Scotland project grant. Professor Berry was supported by a Senior Clinical Fellowship from the Scottish Funding Council.